Peningkatan Literasi Ekonomi Islam Pada Jamaah Masjid Besar Kecamatan Pamulihan - Abdul Hamid; Sutopo s (Yayasan Daarul Huda Kruengmane, 2023)
The Sharia economic industry is experiencing rapid development, with increasingly widespread business opportunities and employment opportunities in various business sectors. However, understanding of Sharia economics is still not evenly distributed across all levels of society in this country. In fact, the Indonesian Government has aspirations to make Indonesia the center of the global Sharia economy. One effort to make this happen is through socialization or organizing programs to introduce Sharia economics to various groups. The Faculty of Economics and Business, Sebelas April University has committed to the community by holding sharia economic education activities in the community. The aim of this community service program is to increase students' awareness and concern for Sharia economics and to deepen them in the basic concepts of Islamic economics which can be applied in everyday life, in the work environment, and within themselves.